Understanding selectivity in organic reactions through density functional theory - de Lescure, Louis Raymond Philibert, author; Paton, Robert, advisor; McNally, Andrew, advisor; Bandar, Jeffrey, committee member; Kennan, Alan, committee member; Herrera-Alonso, Margarita, committee member (Colorado State University. Libraries, 2024)
The success of chemical reactions is often expressed through the lens of selectivity, defined as the preference for a desired reaction pathway over an undesirable one. A profound understanding of the rationale behind the selectivity of chemical reactions is crucial for the progression of synthetic methodologies in organic chemistry. Utilizing quantum chemical approximations, density functional theory (DFT) calculations offer unparalleled insights into the electronic structures and mechanisms of reactions, which can be correlated with observed empirical selectivities. This dissertation demonstrates the significant utility of DFT, in tandem with experimental evidence, in elucidating the intricate mechanisms of reactions. Chapter 1 defines the thematic and methods used throughout this thesis. Chapters 2 and 3 detail collaborative work with the McNally group at Colorado State University. Here, we developed innovative methods for the halogenation of pyridines and advanced modifications of pyrimidine rings utilizing redesigned Zincke chemistry. This chapter focuses on the factors influencing the regioselectivity of halogenation processes and provides mechanistic insights into the formation of crucial intermediates. Chapter 3 outlines a joint project with the Race group at the University of Minnesota, where we explored the homologation of benzylic carbon-bromide bonds. Our investigations centered on the ring-opening of phenonium intermediates, a critical step in determining the success of the reaction. Chapter 4 presents a collaboration with the Aggarwal group at the University of Bristol. This chapter examines the nuanced interplay between kinetic and thermodynamic factors that govern the enantioselectivity of the reaction discussed. This comprehensive study underscores the integration of theoretical and experimental approaches in advancing our understanding of complex chemical reactions.
Keywords: reaction mechanism; DFT